2014
DOI: 10.1088/1742-6596/500/5/052046
|View full text |Cite
|
Sign up to set email alerts
|

Reactive atomistic simulations of shock-induced initiation processes in mixtures of ammonium nitrate and fuel oil

Abstract: Abstract. Ammonium nitrate mixed with fuel oil (ANFO) is a commonly used blasting agent. In this paper we investigated the shock properties of pure ammonium nitrate (AN) and two different mixtures of ammonium nitrate and n-dodecane by characterizing their Hugoniot states. We simulated shock compression of pure AN and ANFO mixtures using the Multi-scale Shock Technique, and observed differences in chemical reaction. We also performed a large-scale explicit sub-threshold shock of AN crystal with a 10 nm void fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Additionally, MD simulations have been used to study square pore collapse that produces jetting [31], the effect of shock strength on the mechanism of collapse [32], and the effect of pore size and arrangement on the minimum piston velocity necessary to produce detonation [33]. Reactive cases have been considered in MD simulations with the ReaxFF reactive force field [34,35] for the energetic materials pentaerythritol tetranitrate (PETN) [36] and ammonium nitrate/fuel oil (ANFO) [37]. In both cases it was observed that the presence of pores led to an enhanced chemical reactivity compared to defect-free material.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MD simulations have been used to study square pore collapse that produces jetting [31], the effect of shock strength on the mechanism of collapse [32], and the effect of pore size and arrangement on the minimum piston velocity necessary to produce detonation [33]. Reactive cases have been considered in MD simulations with the ReaxFF reactive force field [34,35] for the energetic materials pentaerythritol tetranitrate (PETN) [36] and ammonium nitrate/fuel oil (ANFO) [37]. In both cases it was observed that the presence of pores led to an enhanced chemical reactivity compared to defect-free material.…”
Section: Introductionmentioning
confidence: 99%
“…6C). This may be related to the presence of fuel oil, which increases contact between particles form by NH 4 NO 3 27, 28. These results question whether the explosive capacity of ANFO samples is modified according to the presence or absence of fossil fuel in the explosive mixture.…”
Section: Resultsmentioning
confidence: 99%
“…MSST is based on the conservation laws, which controls state variables on the Hugoniot line and the Rayleigh line by changing the volume and temperature. Several reports have shown that NEMD and MSST can obtain consistent results (Reed et al, 2010;Thompson and Shan, 2014).…”
Section: Introductionmentioning
confidence: 87%